Non-Steroidal Anti-Inflammatory Drugs Are Inhibitors of the Intestinal Proton-Coupled Amino Acid Transporter (PAT1): Ibuprofen and Diclofenac Are Non-Translocated Inhibitors - Carsten Uhd Nielsen; Sebastian Jakobsen; Maria L. Pedersen (Pharmaceutics)
Background/Objectives: The proton-coupled amino acid transporter (PAT1) is an intestinal absorptive solute carrier responsible for the oral bioavailability of some GABA-mimetic drug substances such as vigabatrin and gaboxadol. In the present work, we investigate if non-steroidal anti-inflammatory drug substances (NSAIDs) interact with substrate transport via human (h)PAT1. Methods: The transport of substrates via hPAT1 was investigated in Caco-2 cells using radiolabeled substrate uptake and in X. laevis oocytes injected with hPAT1 cRNA, measuring induced currents using the two-electrode voltage clamp technique. The molecular interaction between NSAIDs and hPAT1 was investigated using an AlphaFold2 model and molecular docking. Results: NSAIDs such as ibuprofen, diclofenac, and flurbiprofen inhibited proline uptake via hPAT1, with IC50 values of 954 (logIC50 2.98 ± 0.1) µM, 272 (logIC50 2.43 ± 0.1) µM, and 280 (logIC50 2.45 ± 0.1) µM, respectively. Ibuprofen acted as a non-competitive inhibitor of hPAT1-mediated proline transport. In hPAT1-expressing oocytes, ibuprofen and diclofenac did not induce inward currents, and inhibited inward currents caused by proline. Molecular modeling pointed to a binding mode involving an allosteric site. Conclusions: NSAIDs interact with hPAT1 as non-translocated non-competitive inhibitors, and molecular modeling points to a binding mode involving an allosteric site distinct from the substrate binding site. The present findings could be used as a starting point for developing specific hPAT1 inhibitors.